Preparation, characterization and thermal dehydration kinetics of titanate nanotubes - Yilmaz, Muge Sari; Kasap, Sibel; Piskin, Sabriye (SPRINGER, 2013)
Titanate nanotubes were synthesized utilizing the hydrothermal method using titanium dioxide nanoparticles. The experiments were carried out considering the process as a function of reaction temperature, time, NaOH concentration and the acidity of the washing solution. The formation of titanate nanotubes was shown to be affected strongly by variations in any parameter. The optimum conditions for the synthesis of titanate nanotubes were determined to be a reaction temperature of 190 A degrees C, and a reaction time of 12 h, using 10 M NaOH concentration and the washing solution to have a pH of 5.5. In addition, thermogravimetric analysis (TG/DTG) was used to investigate the thermal behaviour and dehydration kinetics of titanate nanotubes. In order to better understand their thermal behaviour, the thermal analysis of bulk hydrogen trititanate was performed. The values of the apparent activation energies of the first and second dehydration stages for titanate nanotubes were 81.44 +/- A 15.85 and 82.69 +/- A 7.46 kJ mol(-1), respectively. The values of the apparent activation energies of the first, second and third dehydration stages for bulk hydrogen trititanate were 115.93 +/- A 5.40, 137.58 +/- A 6.47 and 138.97 +/- A 8.47 kJ mol(-1), respectively.
Keywords: Titanate nanotubes; Bulk hydrogen trititanate; Dehydration kinetics; Model-free method; HYDROTHERMAL TREATMENT; TITANIUM; Thermodynamics; Chemistry